Agroforestry and climate change : issues and challenges - Jhariya, Manoj Kumar; Yadav, Dhiraj Kumar; Banerjee, Arnab (Professor of environmental science) (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2020)
"This volume, Climate Change and Agroforestry System: Adaptation and Mitigation Strategies, addresses the burning issues of the impact of climate change, the alteration of environmental quality, and subsequent mitigation and adaptation strategies through various agroecosystem practices, primarily in agroforestry. It provides new insights in the field of role of agroecosystems toward combating the negative impact of climate change as well as maintaining the sustainability of ecosystem. The book discusses in depth the impact of climate change on forests and other agroecosystems. It presents new research on mitigation strategies, looking at carbon sequestration in agricultural soils, environmental greening, natural resource management, and livelihood security. It provides a thorough analysis of the potential of various modern, improved, and scientific farming practices, such as climate-smart agriculture and agroforestry systems for climate change mitigation and adaptation. The book also examines the invasion of major fungal diseases in forests and agricultural crops due to climatic fluctuations and goes on to look at water and waste management practices. The updated information and recent developments found in this volume will be valuable for researchers, policymakers, faculty, and students in the field of forestry, agroforestry, environment, ecology, and natural resources"--
OCLC-licensed vendor bibliographic record.
Keywords: Agroforestry -- Climatic factors; SCIENCE / General; TECHNOLOGY / Agriculture / Forestry